The role of the arginine residue in site RC for the analgesic activity of the recombinant Chinese scorpion Buthus martensii Karsch, BmK AGP-SYPU1. (June 2018) - Cui, Yong; Wang, Yao; Wang, Xuelin; Zhang, Zhengwei; Zhang, Jinghai; Zhao, Yongshan
Graphical abstract: Arg58 in BmK AGP-SYPU1 is an important modulator for the whole structure. Highlights: Arginine residue at position 58 in Bmk AGP-SYPU1 is important for its analgesic effect. CD spectra were performed to monitor the secondary structure of the protein. The loop between the β2 and β3 sheet could be affected by the residue 58. Abstract: Scorpion venom is composed of a large number of bioactive peptides which display important pharmacological activities. In this study we have carried out a study of the functional role of the arginine residue at position 58 in the site RC comprising the reverse turn (8–12) and C-terminal residues 58–64. A polymerase chain reaction was used to substitute this arginine residue with a single amino acid such as alanine, glycine and lysine. The mutants were expressed in soluble form in E. coli, and purified by affinity chromatography. After target peptide purity identification, the recombinant peptides underwent a circular dichroism analysis and a study of their analgesic activity in mice. The results indicated that a single residue modification can affect the pharmacological activity. Our efforts establish a sound basis for further study of the structure-function determinants of the analgesic effect.